Chrysobalanaceae: Secondary metabolites, ethnopharmacology and pharmacological potential - Carnevale Neto, Fausto [UNESP]; Pilon, Alan Cesar [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Castro-Gamboa, Ian [UNESP] (Springer Nature, 2013)
Many Chrysobalanaceae species, in special Licania and Parinari, are widely used in folk medicine to treat several diseases. This review describes some aspects of their ethnopharmacology potential, biological activities and the secondary metabolites reported so far for Chrysobalanaceae. The chemical constituents of this family include triterpenoids, diterpenoids, steroids and phenylpropanoids like flavonoids as well as chromones derivatives. © 2012 Springer Science+Business Media Dordrecht.
Keywords: Chrysobalanaceae; Ethnopharmacology; Glycoside flavonoid; Kaurane diterpene; Triterpene; chromone derivative; Chrysobalanus grandiflora extract; Chrysobalanus icaco extract; clerodane diterpenoid; Couepia pplyandra; diterpenoid; flavonoid; glibenclamide; kaurane derivative; kaurane triterpenoid; Licania kallunkiae extract; Licania pittieri extract; Licania tormentosa extract; lupane triterpenoid; Magnistipula butayei extract; Maranthus floribunda; myricetin; natural product; oleanane triterpenoid; Parinari capensis extract; Parinari caratellifolia extract; Parinari excelsa extract; phenylpropanoid; plant extract; quercetin; quercetin derivative; steroid; triterpenoid; unclassified drug; unindexed drug; ursane triterpenoid; biochemical composition; biological activity; drug cytotoxicity; ethnopharmacology; human; insulin dependent diabetes mellitus; Licania; metabolite; nonhuman; Parinari; priority journal; review; traditional medicine